Campus-Based Financial Aid Programs: Trends and Alternative Allocation Strategies. (June 2017) - Kelchen, Robert
Two federal campus-based financial aid programs, the Supplemental Educational Opportunity Grant (SEOG) and the Federal Work-Study Program (FWS), combine to provide nearly US$2 billion in funding to students with financial need. However, the allocation formulas have changed little since 1965, resulting in community colleges and newer institutions getting much smaller awards than long-standing private colleges with high costs of attendance. I document the trends in campus-level allocations over the past two decades and explore several different methods to reallocate funds based on current financial need while limiting the influence of high-tuition colleges.